2011
DOI: 10.1007/s11090-011-9286-3
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Discharge for Polysiloxane Thin Films Deposition and Comparison with Low Pressure Process

Abstract: An atmospheric pressure dielectric barrier plasma discharge has been used to study a thin film deposition process. The DBD device is enclosed in a vacuum chamber and one of the electrodes is a rotating cylinder. Thus, this device is able to simulate continuous processing in arbitrary deposition condition of pressure and atmosphere composition. A deposition process of thin organosilicon films has been studied reproducing a nitrogen atmosphere with small admixtures of hexamethyldisiloxane (HMDSO) vapours. The pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 48 publications
0
41
0
2
Order By: Relevance
“…In Figure 31, the deposition rates of HMDSO discharges within two different LP reactors (with a deposition area of 180 and 1500 cm 2 ) using a monomer gas flow of 4 and 28 sccm are depicted. AP conditions found comprise DBDs with 1-4 sccm HMDSO (in 10 slm He), 15 cm in diameter, and with 1-24 sccm HMDSO (in 2 slm N 2 ) using a 23 cm long rod and a rotating ground electrode (34,114). This is caused by different eedfs and incorporation rates as discussed earlier (14,67).…”
Section: Atmospheric Pressure Plasmasmentioning
confidence: 87%
“…In Figure 31, the deposition rates of HMDSO discharges within two different LP reactors (with a deposition area of 180 and 1500 cm 2 ) using a monomer gas flow of 4 and 28 sccm are depicted. AP conditions found comprise DBDs with 1-4 sccm HMDSO (in 10 slm He), 15 cm in diameter, and with 1-24 sccm HMDSO (in 2 slm N 2 ) using a 23 cm long rod and a rotating ground electrode (34,114). This is caused by different eedfs and incorporation rates as discussed earlier (14,67).…”
Section: Atmospheric Pressure Plasmasmentioning
confidence: 87%
“…At the same time, it led to a decrease in desired groups. Many studies showed the effect of plasma polymerization power on the contact angle of the resulting coating [85,86].…”
Section: Ii-4-2-influence Of Input Power On Wettabilitymentioning
confidence: 99%
“…Siliprandi et al [85] showed the decrease of the degree of polymerization and formation implies growth in itself (oligomer-like layer) at low input power. As well, the smooth structure was deposited in ultra-low fragmentation conditions.…”
Section: Ii-4-2-influence Of Input Power On Wettabilitymentioning
confidence: 99%
“…In the last years, atmospheric pressure plasma treatments have gained considerable popularity for the surface modification of materials [1,[26][27][28]. The main advantages over the low-pressure ones are the possibility to avoid the expensive vacuum systems, to decrease the time of treatment, and to simplify the technological transfer where the processes of production are making in continuous mode.…”
Section: Introductionmentioning
confidence: 99%